2023
DOI: 10.1002/aelm.202201081
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Electrical ReRAM Device Degradation Induced by Thermal Cross‐Talk

Abstract: A switching of resistive memory cells leads to a local accumulation of Joules heat in the device. In resistive RAM (ReRAM) arrays, the heat generated in one cell spreads via common electrode metal lines to the neighboring cells and may cause their performance degradation. The performance degradation results in reduced number of switching cycles and, in extreme cases, even in a loss of a bit, caused by the rupture of the nanofilament. The authors propose a thermal analysis of the thermal cross‐talk, describe it… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…47 However, the matrix of the oxide layer in ReRAM is typically insulating, and the filament phase is often chemically and thermally unstable, leading to poor data retention properties. 48,49 In contrast, the CrN memory device in this study combines the benefits of phase change in PCRAM and the thermally induced atomic diffusion process in ReRAM, providing a promising approach to addressing the challenges of the high-energy-budget melting process in PCRAM and the poor thermal stability of ReRAM simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…47 However, the matrix of the oxide layer in ReRAM is typically insulating, and the filament phase is often chemically and thermally unstable, leading to poor data retention properties. 48,49 In contrast, the CrN memory device in this study combines the benefits of phase change in PCRAM and the thermally induced atomic diffusion process in ReRAM, providing a promising approach to addressing the challenges of the high-energy-budget melting process in PCRAM and the poor thermal stability of ReRAM simultaneously.…”
Section: Resultsmentioning
confidence: 99%
“…The local temperature at the thinnest part of the filament can reach temperature in excess of 1084°C [37]. 1084°C is the melting temperature of Cu (see Table 1) and melting of Cu electrodes has been experimentally observed after excessive heating of a ReRAM cell [38]. At such high temperature, the Cu atoms of the Cu CF diffuse out, may undergo the redox reaction in TaO x , and are returned as Cu + ions by the electric drift fields back to the Cu electrode or stay immobilized in TaO x material.…”
Section: Electric Characteristics Of the Ruthenium (Cu/tao X /Ru)mentioning
confidence: 99%
“…In Ref. [30], it has been experimentally observed that frequent switching of a ReRAM cell leads to the incipient melting of the Cu electrodes including Cu pads. This gives a definite reference point for the local temperature of 1085°C, which is the melting temperature of copper.…”
Section: A Schematic Resistive Random Access Memory (Reram) Crossbar ...mentioning
confidence: 99%
“…To make practical use of Eq. ( 5), we avail ourselves of a valuable experimental reference [30] that can be used to calibrate Eq. ( 5).…”
Section: Prediction and Verification Of Reram Devices' Electric Degra...mentioning
confidence: 99%
See 1 more Smart Citation